Statistics Flip-Worksheet: The Key to Improve Students' Critical Thinking Skill - Febriani, Indri Rohmatul Fakhri; Rahaju, Endah Budi; Ekawati, Rooselyna; Shodikin, Ali (Universitas Negeri Surabaya, 2024)
Abstract The addition of flip-worksheets to the statistics curriculum is anticipated to enhance students' capacity for critical thinking. This research is a development research that aims to create a worksheet supported by a Flipbook that is reliable and useful for teaching statistics and could influence students' critical thinking skill. Some exercises and open-ended questions from the provided infographics are included in the Flip-Worksheet. The worksheet uses mean, median, and modus material. The flip-worksheet was created during a formative evaluation stage with 15 junior high school students in the eighth grade. Data was analyzed using walkthroughs, questionnaires, interviews, and document reviews. According to the validation results, Flip-Worksheet is extremely valid in terms of media (89.58%), and it is valid in terms of material (79.43%). The practicality percentage was 90.74%. It is in an interval between 80% - 100% which falls into the very practice category. The N-gain value was 0.71. The grade VIII student's capacity to think critically increased as a result of using the Flip-worksheet which had high criteria. Additionally, based on the document analysis of students' responses about the process of interpretation, analysis, assessment, inference, explanation, and self-regulation on a variety of critical thinking tasks, it may have the effect of developing students' critical thinking abilities. It can be used as a learning medium and can develop critical thinking skills needed in the 21st century. It is hoped that next studies of learning media will be conducted in the future to enhance critical thinking abilities with other technologies.